An Evaluation towards the Service Quality for the Tourism Sector in the East Coast Economic Region (ECER), Malaysia - Mohd Saiful Izwaan Saadon; Aleff Omar Shah Nordin; Nur Amalina Mohamad Zaki; Tan Owee Kowang; Norshahrizan Nordin (International Journal of Supply Chain Management, 2019)
Abstract— In theory, the integration of Kano Model and SERVQUAL into Quality Function Deployment is to remove the assumption of linear and to offer innovative input. Kano Model characterizes attributes for product or services based on the level of customer satisfaction towards the attributes. Indirectly it can facilitate SEVQUAL to determine level of priority to the improvement process required by the organisation based on certain categories requested, in which this is going towards into the improvement of customer satisfaction. Kano Model also enables SERVQUAL to focus on interesting attributes and it is popular in the service innovation process. According to the theory, the process of the integration of Kano Model and SERVQUAL into QFD will allow us to construct a model of service quality for the tourism sector which can satisfy customer’s needs and wants. This will grant a high level of customer satisfaction. This study can determine attributes according to the categories of basic needs, performance needs and excellence needs. By doing so, we eventually will be able to determine basic elements, performance elements and the excellent elements for the service quality for the tourism sector. These dimensions can be a reference to organisations when they plan their activities for their activities related to the service quality in the future. Keywords— Kano Model, SERVQUAL, Quality Function Deployment, Tourism Sector.